INCREASING STUDENTS' LEARNING MOTIVATION THROUGH INSTAGRAM MEDIA IN WRITING CAPTIONS AT SENIOR HIGH SCHOOL STUDENTS (psnppg, 2023)
The objective of this research is to figure out is there any increasing in students' motivation andlearning outcomes in writing captions after learning using Instagram media. The data werecollected by applying test and questionnaire. The subject of this research were 36 students from classXI-D2 whom the researcher followed their Instagram. The result of this research showed that thestudents’ writing caption ability was varied. In the pre-test, there were only 4 students who passedthe completeness limit. After carrying out the cycle 1 post-test, students who achieved completenessincreased to 27 students or 75% of the total number. The score results from the implementation ofpost-test cycle 2 showed an increase in 36 students who achieved completeness. To conclude, thestudents’ abilities in writing caption on Instagram are fairly good, even though there were elementsneed to be improved.
Keywords: Writing; caption; Instragram